EFL teachers' cognitions about pronunciation in Cyprus. Issue 6 (3rd July 2019) - Georgiou, Georgios P.
ABSTRACT: Neglecting pronunciation in the instruction of foreign languages is quite common both worldwide [Derwing, T. M., and M. J. Murno, 2005. "Second Language Accent and Pronunciation Teaching: A Research-Based Approach." TESOL Quarterly 39 (3): 379–397] and in Greek-Cypriot classrooms [Kyprianou, M. 2015. "Teaching and Learning English Pronunciation in Cyprus: Survey, Analysis and Challenges." PhD diss., University of Cyprus]. The present study aims to investigate cognitions, challenges and practices of various age groups of English as a Foreign Language (EFL) teachers in Cyprus in relation to the teaching of pronunciation in an effort to interpret the low interest that pronunciation receives into classroom. To this purpose, 98 Greek-Cypriot EFL teachers were divided into three groups according to their age and they were called to complete an online survey. The results indicated that the older age groups reported different cognitions in relation to the youngest group; e.g. they believed that other teaching aspects are more important than pronunciation. Also, the three groups faced many similar challenges in the teaching of pronunciation such as limited time and lack of training, and they were using pronunciation practices almost in the same extent. Implications are drawn regarding the development of a stronger EFL pronunciation teaching in the Greek-Cypriot public schools.